Russian Federation : Country Financial Accountability Assessment - World Bank (Washington, DC, 2013)
This CFAA concentrates, by design, on federal-level public sector financial management in the Russian Federation. Its results feed into the fiduciary discussion presented in the new Russian Federation Country Assistance Strategy (CAS), and into the Core Integrative Fiduciary Assessment (CIFA). In budget management the CFAA recommends 1) strengthening the strategy phase of budget preparation to link macroeconomic resource constraints and sectoral and program targets; 2) adopting a uniform, simplified budget coding structure; 3) adopting a more participatory approach to budget planning and formulation; 4) introducing accounting principles by entities with extra-budgetary funds and preparing reports that are compatible with Treasury accounts and fiscal reporting; 5) preparing a program of institutional development for the MOF and applying modem information technology; and 6) amending the chart of accounts (COA) to fully reflect the budget classification. The development and implementation of a full-function Treasury system will take several years and is not expected to become fully operational before 2004/05. In the interim, the CFAA recommends immediate implementation of an improved system of expenditure monitoring, extension of Treasury control of expenditure commitments to all items of the economic expenditure classification, and replacement of weekly cash finding limits by monthly funding of established expenditure commitments. In accounting and financial reporting, some recommendations are to 0 review of existing budget classifications and coding structures and design of a revised structure and COA that conform with the IMF GFS classification; and to integrate the two existing coding systems. To improve internal controls and internal auditing, the report recommends regarding the internal audit as an important management tool, shifting to a new model, based on service orientation and performance/risk assessment, internal audit functions becoming independent from other organizational and functional departments, staff reporting directly to the head of the organization, regulating the entity by an audit charter, and audit functions be carried out by multi-disciplinary teams. As for external audits, the CFAA strongly supports the Chambers' program of institutional and methodological improvements, in particular its preparation of a long- term plan to assess public institutions' performance (value for money) in the use of public funds. Finally, the CFAA finds that the World Bank is adequately discharging its financial management fiduciary responsibilities with respect to its lending operations. The CFAA risk assessment concludes that the current ring-fencing approach to project implementation arrangements should be maintained, recognizing that--based on the effective operationalization of the reforms being introduced in public financial accountability--the present arrangements could in due course be subject to revision.